Increasing The Skills of Kadilajo Village Residents in The Processing of Rice Waste Into Briquette as an Efforts to Realize Economic Independent Villages (Jurnal Bina Desa, 2022)
Kadilajo Village is one of the areas located in Karangnongko District, Klaten Regency, Central Java Province. Kadilajo is dominated by people working as rice farmers. Rice is the main priority for supporting rice fields in Kadilajo village. Rice production every year gives a high number in the production of rice husk waste. So far, rice husk waste has only been used as an ingredient in the soil mixture process, in this case the rice husk waste has not been fully utilized by the people of Kadilajo Village. Seeing the large amount of rice husk waste providing an innovative to processing into briquettes, rice husk waste briquettes can be used as an environmentally friendly alternative fuel and become a product that has a selling value in improving the economy of Kadilajo Village. The purpose of this activity is to train the people of Kadilajo Village to have the ability to manage rice husk waste into briquettes. The method applied is in the form of socialization and training in making briquettes to the people of Kadilajo Village. The results from program the KKN UNNES Giat 2 show that the people of Kadilajo Village, Karangnongko District, Klaten Regency have gained knowledge about the use of rice husk waste in making briquettes as fuel and a source of income for the community. With this activity, the community can take advantage of rice husk waste.Keywords: Briquettes; Community; Husk; Rice; Husk